Surgery of the thyroid: recent developments and perspective (Swiss Medical Weekly, 2015)
In the past century, thyroid surgery has benefited from physiological and technical revolutions. In the early 1900s, the most important aspect of thyroidectomy was the volume resected, without knowledge of exactly what was removed and if there were important structures around the thyroid gland. The main indications were respiratory problems for tracheal compression and the death rate was greater than 36% due to bleeding, infections, unrecognised bilateral recurrent laryngeal nerve lesions and unrecognised severe hypocalcaemia leading to tetany. At some point this surgery was, therefore, banned in some countries such as France and the United States. Today, thyroid surgery is a common surgery: about 45,000 thyroidectomies are performed per year in France, 60,000 in Germany and 4,000 in Switzerland. Thyroid surgery has become very safe with a mortality of almost 0% and a very low complication rate. In our centre, the number of thyroidectomies has more than tripled in the last decade. There are many indications leading to thyroid surgery, but the three main indications covering 90% of the interventions are cancer (or suspected cancer), hyperthyroidism and size / volume / intrathoracic goitres. In this paper, we highlight some historical points, describe important knowledge and technical improvements made during the last century and give our opinion on expected evolution in this field for the near future.